Applying a participatory methodology to evaluate ecosystem services in the Pampa biome: lessons learned from the Tessa methodology in Uruguay - Schossler, Daniela; Nabinger, Carlos; Ribeiro , Claudio; Boggiano, Pablo; Cadenazzi , Monica; Restrepo-Osorio , Diana (Sustainability in Debate, 2022)
Identifying and measuring ecosystem services involving local stakeholders has been characterised as a novel approach in the literature. This article describes the methodology used in the participatory workshops, the lessons learned, and the specific results of applying the Tessa method. The methodology was piloted with 56 researchers and technicians, more than 22 institutions, and 54 livestock producers involved with the grassland conservation initiative, Alianza del Pastizal. Identified change agents with the most significant impact include the absence of a rural workforce, the lack of family succession, and weeding and overgrazing of grasslands. The primary ecosystem services identified included the production of fodder, meat/wool, wildlife forage, way of life/culture, and medicinal plants. The methodology presented here is replicable, capable of expansion to more groups, contributes to a better understanding, by the producers, of their problems and points to the need for the development of public incentive policies.